1997
DOI: 10.1046/j.1365-2796.1997.00235.x
|View full text |Cite
|
Sign up to set email alerts
|

Narrow hips and broad waist circumferences independently contribute to increased risk of non‐insulin‐dependent diabetes mellitus

Abstract: Abstract. Seidell JC, Han TS, Feskens EJM, Lean MEJ (National Institute of Public Health and the Environment, Bilthoven, the Netherlands, and Royal Infirmary, University of Glasgow, Glasgow, UK). Narrow hips and broad waist circumferences independently contribute to increased risk of noninsulin-dependent diabetes mellitus. J Intern Med 1997; 242: 401-406.Objectives. Patients with non-insulin-dependent diabetes mellitus (NIDDM) have been shown to be more obese and have higher waist-to-hips circumference ratios … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
152
0
2

Year Published

1998
1998
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 185 publications
(171 citation statements)
references
References 16 publications
17
152
0
2
Order By: Relevance
“…Thus, the women in India have a larger waist and smaller hips than expected for their BMI. Given the higher insulin levels in women in India, it is interesting that a large European study has shown that narrow hips and broad waist for a given BMI contribute to increased risk of NIDDM (Seidell et al, 1997). An excess of abdominal fat has been noted in other groups of Asian women, while still of relatively low BMI, for example, women in China showed a tendency to a central pattern of fat distribution (mean WHR¼0.8), while mean BMI was only 20.1-21.9 (Folsom et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the women in India have a larger waist and smaller hips than expected for their BMI. Given the higher insulin levels in women in India, it is interesting that a large European study has shown that narrow hips and broad waist for a given BMI contribute to increased risk of NIDDM (Seidell et al, 1997). An excess of abdominal fat has been noted in other groups of Asian women, while still of relatively low BMI, for example, women in China showed a tendency to a central pattern of fat distribution (mean WHR¼0.8), while mean BMI was only 20.1-21.9 (Folsom et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Large hip circumference is found to be associated with a lower risk of diabetes, independent of BMI and WC (Seidell et al, 1997;Snijder et al, 2003).…”
Section: Introductionmentioning
confidence: 91%
“…Lean et al (1995) proposed WC as a simple measurement to indicate the need for weight management. Several studies found a close relation between WC and cardiovascular risk factors Seidell et al, 1997;Janssen et al, 2002). The Framingham study suggested that the waist predicted mortality better than other anthropometric measures (Higgins et al, 1988).…”
Section: Cardiovascular Ratesmentioning
confidence: 98%
“…First, like FFM, hip or thigh, circumferences have been shown to be inversely associated with health risk. 39,[49][50][51][52][53][54] A greater lean mass in the nonabdominal region (i.e. a higher muscle mass in the gluteofemoral region) may explain the protective effect of a large hip or thigh circumference.…”
Section: Plausibility Of Adjusting Wc For Heightmentioning
confidence: 99%